2007
DOI: 10.1614/ws-07-044.1
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of Three Leguminous Cover Crops with Yellow Nutsedge (Cyperus esculentus) and Smooth Pigweed (Amaranthus hybridus)

Abstract: Greenhouse replacement-series experiments were conducted to evaluate the competitiveness of cowpea, sunn hemp, and velvetbean when grown in combination with yellow nutsedge and smooth pigweed. The effect of the cover crop species on yellow nutsedge tuber production was also evaluated. Cowpea and velvetbean were equally competitive with yellow nutsedge, but sunn hemp was less competitive. Although sunn hemp height was double that of cowpea or velvetbean, photosynthetically active radiation penetrating to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…This research also found that sunn hemp could also tolerate 2,4-DB as a postemergent application (Mosjidis and Wehtje 2011). Imazethapyr was also determined to be safe for use in sunn hemp and effective against yellow nutsedge (Cyperus esculentus L.), which is not well suppressed by sunn hemp (Collins et al 2007;Mosjidis and Wehtje 2011). With advancements in sunn hemp breeding and increased utilization of this species in a broader geographical range, continued research efforts to determine additional herbicide programs will be critical for successful production in the future.…”
Section: Weed Control In Sunn Hemp Productionmentioning
confidence: 73%
See 4 more Smart Citations
“…This research also found that sunn hemp could also tolerate 2,4-DB as a postemergent application (Mosjidis and Wehtje 2011). Imazethapyr was also determined to be safe for use in sunn hemp and effective against yellow nutsedge (Cyperus esculentus L.), which is not well suppressed by sunn hemp (Collins et al 2007;Mosjidis and Wehtje 2011). With advancements in sunn hemp breeding and increased utilization of this species in a broader geographical range, continued research efforts to determine additional herbicide programs will be critical for successful production in the future.…”
Section: Weed Control In Sunn Hemp Productionmentioning
confidence: 73%
“…), and morningglory (Ipomoeae spp.) (Collins et al 2007;Teasdale 1988;White et al 1989). Either as a ground cover or through allelopathy, as noted in subterranean clover (Trifolium subterraneum L.), weed control achieved through legume cover crops has the potential to reduce early-season herbicide use in agricultural systems (Hartwig and Ammon 2002;Leather 1983;Mosjidis and Wehtje 2011).…”
Section: Weed Control With Legume Cover Cropsmentioning
confidence: 99%
See 3 more Smart Citations